Acute enhancement of executive functions through cognitively challenging physical activity games in elementary physical education. (May 2023) - Kolovelonis, Athanasios; Goudas, Marios
This study examined the effects of cognitively challenging physical activity games on students' executive functions and situational interest in physical education. Participants were 144 fourth- and fifth-grade students (75 boys, 69 girls) from four elementary schools. A four-group, repeated measures, cross-over quasi-experimental design was used in this acute experiment including a physical education session. One fourth- and one fifth-grade class from each school were randomly assigned to Group 1 with cognitively challenging physical activity games, Group 2 with a session for teaching soccer skills, Group 3 with a session for teaching track and field skills, and Group 4 (waiting-list control group) with cognitively challenging physical activity games after the post-test. Pre- and post-test measures for executive functions and a post-test measure for situational interest were included. Group 1 students, who were involved in cognitively challenging physical activity games, improved their scores in the executive functions more than students who participated in the sessions with soccer or track and field skills and waiting-list control group students. The positive effects on students' executive functions were replicated when the cognitively challenging physical activity games session was implemented in the waiting-list control group. Some improvements on executive functions for students who participated in the soccer skills session were found. Students who played the cognitively challenging physical activity games reported higher scores on novelty compared to students in the soccer or track and field groups. These results support the effectiveness of the cognitive challenging physical activity games for triggering students' executive functions in physical education.